Incidence of early postoperative ischemic stroke in lumbar discectomy: A retrospective study (Annals of Medical Research, 2021)
Aim: Ischemic stroke (IS) is one of the leading causes of death worldwide. It may cause undesirable neurological sequels. This study aims to determine the incidence of IS in the early postoperative period in patients operated for lumbar disc herniation. Material and Methods: The electronic medical records of patients who underwent elective lumbar disc herniation surgery between January 2017 and August 2019 were reviewed retrospectively. Patients with preoperative infection and neoplastic disease were excluded from the study. Patient demographics, pre and postoperative pain and disability levels, operated disc levels, duration of surgery and hospital stay, and complications were recorded.Results: Of the 179 patients who underwent lumbar microdiscectomy for lumbar disc herniation, a total patient of one (0.55%) patient developed IS in the right cerebellar region in the early postoperative period. The risk factors detected in the patient included hypertension, carotid artery stenosis and therefore irregular use of acetylsalicylic acid. Postoperative infection was detected in two patients (1.12%), peroperative cerebrospinal fluid leak in two patients (1.12%), and recurrent lumbar disc herniation in three patients (1.67%) in the late period. No mortality was observed.Conclusion: In recent years, there has been an increase in minimally invasive spine surgeries, especially in elderly patients at risk of ischemic stroke. It is important to identify and optimize these patients before surgery. While the incidence of ischemic stroke following lumbar microdiscectomy is low, it is necessary to be careful as a high risk of morbidity and mortality is in question.
Keywords: Cerebral stroke; discectomy; incidence; ischemia